Pelaksanaan Perjanjian Keagenan Pada Perusahaan Pelayaran PT. Prima Kaltara Bahari di Tarakan - Budi Handojo; Muhammad Sapdi; Sahudiyono Sahudiyono; PantjaSiwi V R Ingesti; Yudhanita Pertiwi (Majalah Ilmiah Bahari Jogja, 2022)
The purpose of this study is to describe the implementation of agency agreements at PT. Prima Kaltara Bahari shipping lines in representing the Owner / principal; identifying problems in the implementation of the ship agency agreement at PT. Prima Kaltara Bahari shipping lines. This research is a research with a legal approach using a qualitative approach. Furthermore, it applied a descriptive approach in its data analysis. The results showed that the agency agreement between the principal/Owner and the local shipping lines as a local agent began with the appointment of what is commonly called a Letter of Oppoinment. It is a work order from the ship's Owner to the local company agent as stipulated by Ministry Regulation Number 65 of 2019 on the Implementation and Operation of Ship Agency. The implementation of the work as stated in the Letter of Oppoinment must be carried out which includes services before the ship arrives, when the ship arrives (Clearent In) and upon departure of the ship (Clearent Out). This process applied the provisions of Article 1338 of the Civil Code that all agreements made legally and laws to those who make them. It means that the local agent, in this case, PT Prima Kaltara Bahari is bound to fulfill its obligations to the Principal / Owner abroad.